Proceedings of the 2019 European Conference on Computing in Construction 2019
DOI: 10.35490/ec3.2019.184
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the impact of size of uncertainty events on the construction cost of highway projects using ANFIS

Abstract: This study examines the use of Adaptive Neuro-Fuzzy Inference System (ANFIS) as a machine learning technique in the prediction of the impact size of uncertainty events on construction cost of highway projects and whether this technique is more accurate than the classical statistical methods. The rationale for the study stems from the availability of several techniques such as regression analysis and machine learning for developing predictive models of relationships of various variables in the construction indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Machine learning methods including linear regression, support vector machines, and artificial neural networks have been used to estimate building costs in a variety of ways, including preliminary cost assessment (Jaafari, A., Pazhouhan, I., & Bettinger, P., 2021), cost contingency analysis, and risk assessment (Zhang, H., Li, H., Zhu, Y., & Fang, Y., 2019). These studies have shown that machine learning techniques can effectively capture the complex relationships between project parameters and costs, providing more accurate and reliable estimates (Alireza, M., & Abimbola, W., 2019). Despite these promising findings, the application of machine learning in construction cost estimation is still a relatively new area of research, with many studies limited by small sample sizes or narrow scopes (Nguyen Van, T., & Nguyen Quoc, T. , 2021).…”
Section: Machine Learning In Construction Cost Estimationmentioning
confidence: 99%
“…Machine learning methods including linear regression, support vector machines, and artificial neural networks have been used to estimate building costs in a variety of ways, including preliminary cost assessment (Jaafari, A., Pazhouhan, I., & Bettinger, P., 2021), cost contingency analysis, and risk assessment (Zhang, H., Li, H., Zhu, Y., & Fang, Y., 2019). These studies have shown that machine learning techniques can effectively capture the complex relationships between project parameters and costs, providing more accurate and reliable estimates (Alireza, M., & Abimbola, W., 2019). Despite these promising findings, the application of machine learning in construction cost estimation is still a relatively new area of research, with many studies limited by small sample sizes or narrow scopes (Nguyen Van, T., & Nguyen Quoc, T. , 2021).…”
Section: Machine Learning In Construction Cost Estimationmentioning
confidence: 99%